A Dynamic Connectedness Analysis Between Rare Earth Prices and Renewable Energy - Madaleno, Mara; Taskin, Dilvin; Dogan, Eyup; Tzeremes, Panayiotis (Elsevier Sci Ltd, 2023)
Current world environmental challenges put pressure on clean energy produced mostly through renewables. There is an undeniably important role of rare earth minerals in renewable energy technologies. This study aims to infer the relationship between rare earth, clean energy, renewable energy technologies, and carbon emissions, focusing on daily stock price index data and applying the novel quantile time-frequency connectedness model, and the cross-quantilogram dependence approach during 2012-2022. Results show that spillovers among rare earth minerals and renewable energy are dependent on market conditions, time horizons, and analyzed quan-tiles. They also highlight the net receiver role of rare earth, especially in the short term. Findings might help investors understand diversification benefits and support policymakers in developing strategies for lessening import dependence on rare earth metals, as important as they are for renewable technology adoption to ensure green growth.
Madaleno, Mara/0000-0002-4905-2771; Dogan, Eyup/0000-0003-0476-5177; Taskin, Dilvin/0000-0001-6139-8006
Keywords: Rare Earth Minerals; Clean Energy; Renewable Energy Technology